AN OBSERVATIONAL STUDY OF KHALITYA WITH THE HELP OF HAMILTON NORWOOD SCALE IN RELATION EXCESSIVE LAVANA IN DAILY DIET IN SAURASTRA REGION - Prasad J, *Sharma Vishnu; Kalpana, Sathe; Narendra, Yadnik Vd. (International Journal of Ayurveda and Pharma Research, 2015)
Now a day the entire world is optimistically looking in the direction of the Ayurveda for its eternal principles so we will have to prove our principles in modern era. In continuation this study is carried out. Excessive consumption of salt is becoming a leading habit in people in now days; which is disturbing the health of the people progressively. Acharya Charaka had described that if people are consuming excessive salt for long duration, absolutely they will influence with baldness (Khalitya). According to him salt is related with hot and sharp properties. However it is responsible for the accumulation of Doshas if not used properly. Due to hot, sharp and accumulation of Doshas properties it becomes harmful for hairs and causes baldness. To examine and prove the Ayurvedic principle the study was conducted in 30 volunteers having baldness (Khalitya) and salt consumption by them. Baldness was identified with the help of Hamilton Norwood Scale in the volunteers. According to questionnaire approximate salt consumption was assessed of the same volunteers and observed the comparison of baldness grade according to salt consumption. It was observed that the severity of baldness was found greater in higher consumption volunteers rather than normal consumption volunteers less than 5gms/day. According to Hamilton Norwood Baldness grading system severely affected from baldness were consuming excess salt having 80%; and only 20% volunteers are consuming in limits. Which shows that high salt intake is a major risk factor related to baldness. It proves the statement of Acharya Charaka related excess consumption of salt and baldness.